2015
DOI: 10.1021/acs.chemmater.5b03314
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling VO2 Nanonet with High Switching Performance at Wafer-Scale

Abstract: Technologically controlling nanostructures is essential to tailoring the functionalities and properties of nanomaterials. Various methods free from lithography-based techniques have been employed to fabricate 2D nanostructures; however it is still hard to achieve a well interconnected 2D regular nanostructure. Here, we demonstrate a facile chemical solution method to self-assemble a regular and interconnected VO2 nanonet on the wafer scale. The nanonet shows a well-defined 2D truss network constructed by VO2 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 44 publications
2
48
0
Order By: Relevance
“…By the same method, the phase and thickness of VO 2 film can be controlled simply via changing precursor concentration and reaction time . Without the TiO 2 buffer layer, VO 2 nanonet with high switching performance was obtained on sapphire substrate after a short annealing at 400 °C for 30 s in low vacuum condition …”
Section: Hydrothermal Combined Thermal Treatment Synthesis Of Vo2(m)mentioning
confidence: 99%
“…By the same method, the phase and thickness of VO 2 film can be controlled simply via changing precursor concentration and reaction time . Without the TiO 2 buffer layer, VO 2 nanonet with high switching performance was obtained on sapphire substrate after a short annealing at 400 °C for 30 s in low vacuum condition …”
Section: Hydrothermal Combined Thermal Treatment Synthesis Of Vo2(m)mentioning
confidence: 99%
“…The substrates with polarity and crystal orientations were usually used to grow fine organized thin films 26 27 28 . Our recent work has demonstrated that high quality epitaxial VO 2 thin films can be grown on sapphire substrates by hydrothermal method 29 . Compared to the costly single crystal substrate, the buffer layer prepared on glass is an economic way to grow fine films.…”
mentioning
confidence: 99%
“…Meanwhile, the thermomechanical devices like resonator and actuator are based on the crystal contraction along the c ‐axis (≈1%) and expansion on the a ‐axis direction (≈0.6%) when MIT happens . Moreover, as the conductivity of VO 2 changes up to five magnitudes upon the MIT due to the overlapping and separation of energy band in the crystal, the fabrication of temperature sensor and other thermal activated electrical device becomes possible.…”
Section: Thermal Stimulated Devicesmentioning
confidence: 99%